Student evaluation to improve the student learning experience: an Australian university case study - Tucker, Beatrice (Routledge, 2013)
Universities have been collecting student feedback on their experiences in teaching and learning for decades. Their voice is usually captured in surveys, and quantitative and qualitative data are used for quality improvement. Quantitative data are often used to monitor the student experience and used as a key performance measure in universities. This paper describes key drivers influencing the implementation of student evaluation systems in Australia. The case of one university’s approach is used to describe how the student voice, in addition to those of other key stakeholders, is used to analyse and improve the student experience in teaching and learning.